Simulator Arsitektural Dari Sirkuit Elektronis Guna Tujuan Pembelajaran - Suryo Bramasto; Sunarto Sunarto (Faktor Exacta, 2018)
The electronic circuit engineering learning processes generally requires specific infrastructures which sometimes constrained to cost factors in the procurement. Circuit simulator could be an alternative as electronic circuit engineering learning tool. Architectural simulation provides designers the ability to quickly examine a wide variety of design choices. The recent trend in system design toward architectures that react to circuit-level phenomena has outstripped the capabilities of traditional cycle-based architectural simulators. In this paper, a simulator that incorporates a circuit modeling capability, permitting architectural-level simulations that react to circuit characteristics (such as latency, energy, power brightness, or current draw) on a cycle-by-cycle basis is presented. As for learning purpose, circuit template and pre-built circuits for many categories are provided. The environment enables process visualization and simulation of analog and digital circuits. The system enables the creation of many laboratory exercises, which offer students opportunities to follow visually characteristic processes in analog and digital circuits. At this research, Rational Unified Process (RUP) software process model and Object Oriented Programming (OOP) are implemented.Keywords: architectural simulation, circuit simulation, learning, RUP, OOP